Antibiotic Effect on Pseudomonas Aeruginosa Isolated From Patient In Hila City - Murtadha Hamza AjeeL1 , Fatma Moeen Abbas2, Amer Jassim Al-Khafaji3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
In this study, a total of 400 clinical samples were collected from patients different hospitals in hilla city((13.51%) Margin teaching hospital, (27.03%)Al-Hilla teaching hospital,( 43.24%) Babylon hospital for maternity and pediatric and (16.22%)Chest Disease Center) , ( 37 ) isolates were identified as to P. aeroginosa, from 9 (18%) isolates from burn specimen, 7 (14%) isolates from otitis , 5 (10%)isolates from UTI , 4 (8%) isolates from wound , 3(7.5%) was isolated from blood specimen where as 6 (6%)was isolated sputum and only 3 (5%)isolates were detected from skin. The period of collection was extended from January 2019 to June 2019. Also antibiotic susceptibility were preformed using disk employed diffusion and agar utilizing dilution processes. Furthermore , the resistance of isolate to a variety of antibiotics has been investigated and found that these isolate have been resistance to more than one antibiotic : 37(100%) resistance to Cloxacilin , 37(100%) to Amoxicillin /Clavulanic acid, 37(100%) to cefotaxime, 36(97%) to ceftizoxone, 34(92%) to Ceftazidime, 14(37%) to Levofloxacin, 18(49%) to Gentamicin, , 3(8%) to Norfloxacin and 1(3%) to Azetronam.